2009
DOI: 10.1007/s11899-009-0032-3
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer-cell neoplasms

Abstract: The natural killer (NK)-cell neoplasms are rare, representing less than 1% of non-Hodgkin lymphoma, except in Asia and Latin America, where they represent 3% to 6%. NK-cell neoplasms include immature acute leukemias; a blastic NK-cell lymphoma, which is obsolete because of its plasmacytoid dendritic-cell origin; and mature NK neoplasms, comprising extranodal NK/T-cell lymphoma (ENKL), nasal-type; aggressive NK-cell leukemia; and chronic NK-cell lymphoproliferative disorders, which are often reactive. Epstein-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
1
17
0
1
Order By: Relevance
“…Though studies are sparse, natural killer cell malignancies seem to be relatively rare in Caucasians, but the incidence rises significantly in Asian and South American populations [4,5]. One study from China showed that natural killer cell malignancies may account for around 6% of the natural killer and T cell malignancies [6].…”
Section: Introductionmentioning
confidence: 99%
“…Though studies are sparse, natural killer cell malignancies seem to be relatively rare in Caucasians, but the incidence rises significantly in Asian and South American populations [4,5]. One study from China showed that natural killer cell malignancies may account for around 6% of the natural killer and T cell malignancies [6].…”
Section: Introductionmentioning
confidence: 99%
“…One of these was T cells and the other distinct lineage was the basis for the ontogeny of NK cells [3,4]. As NK cells and T cells develop from a common myeloid antigenpositive NK/T bipotential progenitor in the bone marrow, NK cells share similar features with cytotoxic T cells [3,5]. NK cells have large granular lymphocyte morphology and, in humans, express a surface CD3 2 and CD56 þ phenotype [3].…”
Section: Introductionmentioning
confidence: 99%
“…A species previously familiar only to aquarium enthusiasts, the zebrafish has moved into a central role as a unique and flexible model for the study of vertebrate biology, in fields including embryology and neurobiology, and, more recently extending to hematopoiesis, immunology, and infectious disease. 1,2 I n this issue of Blood, Balla et al 3 present a detailed examination of zebrafish eosinophils, an enigmatic leukocyte lineage whose role in promoting homeostasis and host defense remains uncertain despite years of research with more traditional human, mouse, and guinea pig model systems. 4,5 Among the highlights of this article is an exquisite atlas of zebrafish eosinophil morphology; the authors document the isolation of gata2-expressing cells from whole-kidney marrow, coloration with standard cytology stains, and prevalence of eosinophilic myelocytes, metamyelocytes, bands, and polymorphonuclear forms with both light and electron microscopic images.…”
Section: Conflict-of-interest Disclosure: the Author Declares No Compmentioning
confidence: 99%
“…Extranodal NK/T-cell lymphomas (formerly lethal midline granulomas), often present in the nasal region, are usually associated with EBV, and are often poorly responsive to anthracycline-based combination chemotherapies. 2 Although progress has been made with alternative chemotherapy regimens and concurrent radiation therapy, these tumors are still most often fatal when in advanced stage. 3,4 Other EBV-associated tumors, most notably posttransplant lymphoproliferative disease, are responsive to adoptive immunotherapy approaches involving transfer of EBVtargeted T cells.…”
mentioning
confidence: 99%